In this page substitution method in integration we are going see where we need to use this method in integration.
In this method we need to change the function which is defined one variable to another variable. If we have limits then we have to change that too.
Now let us see some example problems to understand this topic.
Problem 1 :
Integrate cos x/(1+sin x)
Solution :
= ∫[cos x/(1 + sin x)] dx
Let U = 1+sin x
Differentiate with respect to x on both sides
du = cos x dx
∫ [cos x/(1+sin x)] dx = ∫ [cos x dx/(1+sin x)]
= ∫ du/u
= ∫ (1/u) du
= log u + C
= log (1+sin x) + C
Problem 2 :
Integrate (6x + 5)/√(3x2+5x+6)
Solution :
= ∫ [(6x + 5)/√(3x²+5x+6)] dx
Let U = 3x2 + 5x + 6
Differentiate with respect to x on both sides
du = (6x+5) dx
= ∫ (6x+5) dx/√(3x2+5x+6)
= ∫du/√u
= ∫ u^(-1/2) du
= u^[(-1/2) + 1]/[(-1/2) + 1] + C
= u^[(-1 + 2)/2]/[(-1 + 2)/2] + C
= u^(1/2)/(1/2) + C
= 2 √u + C
= 2 √(3x2+5x+6) + C
Problem 3 :
Integrate cosec x
Solution :
= ∫ cosec x dx
To solve this problem we have to multiply and divide by (cosec x - cot x)
= ∫ cosec x (cosec x - cot x)/(cosec x - cot x) dx
Let U = (cosec x - cot x)
Differentiate with respect to x on both sides
du = - cosec x cot x - (- cosec² x)dx
du = - cosec x cot x + cosec² x)dx
du = cosec²x- cosec x cot x dx
= ∫ (cosec²x - cosec x cot x) dx /(cosec x - cot x)
= ∫ du/u
= ∫ (1/u) du
= log u + C
= log (cosec x - cot x) + C
Problem 4 :
Integrate x5 (1 + x6)7
Solution :
Let t = 1 + x⁶
differentiate with respect to x
dt = 6 x⁵ dx
dt/6 = x⁵ dx
x⁵ dx = dt/6
= ∫ x⁵ (1 + x⁶)⁷ dx
= ∫ t⁷ (dt/6)
= (1/6) t⁷ dt
= (1/6) [t(7+1)/(7+1)] + C
= (1/6) (t8/8) + C
= (1/48) t8 + C
= t8/48 + C
= (1 + x⁶)⁸/48 + C
Problem 5 :
Integrate (2Lx + m)/(Lx² + mx + n)
Solution :
Let t = (Lx2+mx+n)
differentiate with respect to x
dt = (2Lx + m) dx
= ∫ (dt/t)
= log t + C
= log (Lx² + mx + n) + C
Problem 6 :
Integrate (4ax + 2b)/(ax2 + bx + c)10
Solution :
t = ax2+bx+c
differentiate with respect to x
dt = 2ax+b
= ∫(4ax+2b)/(ax2+bx+c)10 dx
now we are going to take 2 from the numerator
= ∫ 2 (2ax+2b)/(ax2+bx+c)10 dx
= ∫2 (dt/t10)
= ∫2 t-10 dt
= 2t(-10+1)/(-10+1) + C
= 2t-9/(-9) + C
= (-2/9) (ax2 + bx + c)^(-9) + C
= [-2/9(ax2+bx+c)9] + C
Problem 7 :
∫ 3t2 (t3 + 4)5 dt
Solution :
∫3t2 (t3 + 4)5 dt
Let u = t3 + 4
du = (3t2 + 0) dt
du = 3t2 dt
∫ 3t2 (t3 + 4)5 dt = ∫u5 du
= u6/6 + C
= (t3 + 4)6 / 6 + C
Problem 8 :
∫ √(4x - 5) dx
Solution :
∫ √(4x - 5) dx
Let t = 4x - 5
dt = 4 dx
dx = (1/4) dt
∫ √(4x - 5) dx = ∫ √t (1/4) dt
= (1/4)∫ √t dt
= (1/4) ∫t1/2 dt
= (1/4) t(1/2) + 1 / [(1/2) + 1] + C
= (1/4) t(3/2) / (3/2) + C
= (1/4) t(3/2) x (2/3) + C
= (1/6) t(3/2) + C
= (1/6) (4x - 5)(3/2) + C
Problem 9 :
∫ t2 (t3 + 4)-1/2 dt
Solution :
∫ t2 (t3 + 4)-1/2 dt
Let u = t3 + 4
du = 3t2 dt
t2 dt = (1/3) du
∫ t2 (t3 + 4)-1/2 dx = ∫ u-1/2 (1/3) du
= (1/3)∫ u-1/2 du
Applying the value of u.
= (1/3) u 1/2/(1/2) + C
Problem 10 :
∫ sin10 x cos x dx
Solution :
∫ sin10 x cos x dx
Let sin x = t
cos x dx = dt
∫ sin10 x cos x dx = ∫ t10 dt
= t11/11 + C
Applying the value of t.
= sin11 x / 11 + C
Problem 11 :
∫ (sin x/cos5 x) dx
Solution :
∫ (sin x/cos5 x) dx
Let cos x = t
-sin x dx = dt
sin x dx = -dt
∫ (sin x/cos5 x) dx = ∫ (-dt/t5)
= -∫ (1/t5) dt
= - ∫t-5 dt
= - (t-5 + 1) / (-5 + 1) + C
= - (t-4) / (-4) + C
= - (t-4) / (-4) + C
= - 1/4t4 + C
Applying the value of t, we get
= (- 1/4)cos4x + C
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Dec 21, 24 02:20 AM
Dec 21, 24 02:19 AM
Dec 20, 24 06:23 AM